A single, clinically relevant dose of the GABAB agonist baclofen impairs visuomotor learning. (4th November 2020) - Johnstone, Ainslie; Grigoras, Ioana; Petitet, Pierre; Capitão, Liliana P.; Stagg, Charlotte J.
Abstract : Key points: Baclofen is a GABAB agonist prescribed as a treatment for spasticity in stroke, brain injury and multiple sclerosis patients, who are often undergoing concurrent motor rehabilitation. Decreasing GABAergic inhibition is a key feature of motor learning and so there is a possibility that GABA agonist drugs, such as baclofen, could impair these processes, potentially impacting rehabilitation. Here, we examined the effect of 10 mg of baclofen, in 20 young healthy individuals, and found that the drug impaired retention of visuomotor learning with no significant effect on motor sequence learning. Overall baclofen did not alter transcranial magnetic stimulation‐measured GABAB inhibition, although the change in GABAB inhibition correlated with aspects of visuomotor learning retention. Further work is needed to investigate whether taking baclofen impacts motor rehabilitation in patients. Abstract: The GABAB agonist baclofen is taken daily as a treatment for spasticity by millions of stroke, brain injury and multiple sclerosis patients, many of whom are also undergoing motor rehabilitation. However, decreases in GABA are suggested to be a key feature of human motor learning, which raises questions about whether drugs increasing GABAergic activity may impair motor learning and rehabilitation. In this double‐blind, placebo‐controlled study, we investigated whether a single 10 mg dose of the GABAB agonist baclofen impaired motor sequence learning and visuomotor learning in 20 young healthy participants of both sexes. Participants trained on visuomotor and sequence learning tasks using their right hand. Transcranial magnetic stimulation (TMS) measures of corticospinal excitability, GABAA (short‐interval intracortical inhibition, 2.5 ms) and GABAB (long‐interval intracortical inhibition, 150 ms) receptor activation were recorded from left M1. Behaviourally, baclofen caused a significant reduction of visuomotor aftereffect ( F 1, 137.8 = 6.133, P = 0.014) and retention ( F 1, 130.7 = 4.138, P = 0.044), with no significant changes to sequence learning. There were no overall changes to TMS measured GABAergic inhibition with this low dose of baclofen. This result confirms the causal importance of GABAB inhibition in mediating visuomotor learning and suggests that chronic baclofen use could negatively impact aspects of motor rehabilitation. Key points: Baclofen is a GABAB agonist prescribed as a treatment for spasticity in stroke, brain injury and multiple sclerosis patients, who are often undergoing concurrent motor rehabilitation. Decreasing GABAergic inhibition is a key feature of motor learning and so there is a possibility that GABA agonist drugs, such as baclofen, could impair these processes, potentially impacting rehabilitation. Here, we examined the effect of 10 mg of baclofen, in 20 young healthy individuals, and found that the drug impaired retention of visuomotor learning with no significant effect on motor sequence learning. Overall baclofen did not alter transcranial magnetic stimulation‐measured GABAB inhibition, although the change in GABAB inhibition correlated with aspects of visuomotor learning retention. Further work is needed to investigate whether taking baclofen impacts motor rehabilitation in patients.